Optimalisasi Pengelolaan Limbah Tahu Menjadi Biogas Menuju Desa Mandiri Energi - Nanang Apriandi MS; Lily Maysari Angraini; Nurul Qomariyah (Unram Journal of Community Service, 2021)
Optimization of tofu waste management in Danger Village masbagik kemacatan East Lombok district has been done. Danger village is a village that focuses its economic sector on home indutrsi tofu making. Almost 50% of the total population in the village is involved in this field. Tofu waste, both solid waste and liquid waste, which was initially only disposed of and caused a foul smell, has now been optimally processed into biogas. This new energy source can be used by citizens as fuel for production. The purpose of this activity aims to improve the skills of citizens designing and building household-scale digesters in order to optimize the management of waste tofu into biogas. The method of activity used is focus discussion group to need assement problems that exist in the citizens, and then transfer biogas technology by providing assistance to citizens as partners ranging from digester making to slury management of biogas waste. The result of this activity is the establishment of household-scale digesters in partners and increased understanding of partners related to the use of waste tofu both solid and liquid to become biogas and the realization of the concept of energy independent villages